2019
DOI: 10.18203/2394-6040.ijcmph20195085
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviour and its determinants among rural population- a cross sectional study in South India

Abstract: Despite improvements in access to health care in India, inequalities related to socioeconomic status, geography and gender continue to exist. This is further compounded ABSTRACT Background: Remedial action that a person takes to treat his or her perceived illnesses, is called health-seeking behaviour. Understanding health seeking behaviour (HSB) in a community and the factors which influence their decision, are crucial for planning a "need based" comprehensive health care programmes for the people, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The present study showed that the participants preferred private hospitals over government hospitals which is similar to a study conducted by Dominic ARet al 1224 4 .In contradictory to the studies conducted by Kumar et al and Kumar Det al where the preferred type of health care preferred was Government health facilities. 5,6 This may be due the easy accessibility and feasibility of the private hospital when compared to government settings.…”
Section: Discussionsupporting
confidence: 83%
“…The present study showed that the participants preferred private hospitals over government hospitals which is similar to a study conducted by Dominic ARet al 1224 4 .In contradictory to the studies conducted by Kumar et al and Kumar Det al where the preferred type of health care preferred was Government health facilities. 5,6 This may be due the easy accessibility and feasibility of the private hospital when compared to government settings.…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted by Ramana et al in urban slum of Vishakhapatnam city concluded that private sectors are preferred as a choice by the community people due to various reasons like easy availability, speciality clinics and quality care for acute and chronic illness, particularly by those who don't have financial constraints. 10 In the present study, most of the study participants reported to visit the public and private health facilities for cold/fever 30.4% and musculoskeletal problems/ osteoarthritis 19.6%. Other common morbid conditions for healthcare visit are respiratory problems, injuries/accidents and other communicable diseases.…”
Section: Discussionmentioning
confidence: 49%
“…[ 41 ] A study conducted in Southern India showed that the majority of families (48.15%) preferred to visit government hospitals, whereas the majority of those who visited private doctors (55.54%) favored the allopath system of medicine. [ 42 ] Dependency on “Quacks” is reported to be due to easy access, availability of medicine on the spot, reduced transaction cost as compared with Govt. health centers, level of trust in “Quacks” and private practitioners from earlier favorable results, and non-availability of qualified doctors at the public facilities.…”
Section: Discussionmentioning
confidence: 99%